EFFECTS OF FIRE ON STRUCTURE AND COMPOSITION OF VEGETATION COMMUNITY IN PINE FORESTS, NAM NAO NATIONAL PARK, THAILAND - Kobsak Wanthongchai; Voradet Tarusadamrongdet (BIOTROPIA, 2020)
Anthropogenic forest fires, including those occurring in the pine forests of Thailand, have been widely reported. Although pine forests are fire-dependent, too frequent burning could be unhealthy for the forest as it might result in nutrient depletion and ecosystem degradation. Hence, this study aimed to examine the effects of forest fire on the vegetation structure and composition of a degraded pine forest (PF) and a mixed pine-oak forest (O-PF) in Phu Kum Khao, Nam Nao National Park, Phetchabun Province, Thailand. The effects of fire over one year were studied using three 50 × 50 m experimental plots established in each forest type. Results showed that fire events caused a significantly higher tree mortality rate in the degraded pine forest than in the mixed pine-oak forest. Moreover, the seedling ratio (number of sprouts to number of seedlings) in the mixed pine-oak forest was higher than in the degraded pine forest. Although the sapling and seedling diameters were slightly different between the sites, no significant effect of burning was observed on sapling and seedling density, diameter, or height. This might be due to the high variation of fire behavior in each plot. Since forest fires are a potential factor contributing to forest degradation in the study area, further studies on the effects of fire frequency on vegetation structure and composition are needed to provide sufficient control measures for efficient forest fire management and prevent further ecosystem degradation.